Proceedings of the 5th International Conference on Electrical Engineering and Information Technologies for Rail Transportation (EITRT) 2021 Rail Transportation System Safety and Maintenance Technologies - Qin, Yong.; Jia, Limin; Liang, Jianying; Liu, Zhigang; Diao, Lijun; An, Min.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book reflects the latest research trends, methods, and experimental results in the field of electrical and information technologies for rail transportation, which covers abundant state-of-the-art research theories and ideas. As a vital field of research that is highly relevant to current developments in a number of technological domains, the subjects it covered include intelligent computing, information processing, communication technology, automatic control, etc. The objective of the proceedings is to provide a major interdisciplinary forum for researchers, engineers, academicians, and industrial professionals to present the most innovative research and development in the field of rail transportation electrical and information technologies. Engineers and researchers in academia, industry, and government will also explore an insightful view of the solutions that combine ideas from multiple disciplines in this field. The volumes serve as an excellent reference work for researchers and graduate students working on rail transportation and electrical and information technologies.
Research on Alarm Correlation Analysis for EMU Train Based on Association Rule Mining Algorithm -- System Resilience Assessment Method of Urban Rail Transit Train Traction System Base on RSI -- A Multi-dimensional Health Index Calculation Algorithm for ZPW-2000A Track Circuit -- The Fault Diagnosis Method of Rolling Bearing Based on CEEMDAN.
Keywords: Transportation engineering; Traffic engineering; Computational intelligence; Control engineering; Application software; Transportation Technology and Traffic Engineering; Computational Intelligence; Control and Systems Theory; Computer and Information Systems Applications; Electric railroads -- Congresses; Railroads -- Information technology -- Congresses; Railroads -- Communication systems -- Congresses